원통형 수증기 개질기의 열적조건 변화에 따른 개질성능 평가 - 한훈식; 김서영; 강상우 (대한설비공학회, 2014)
The experimental performance evaluation of a cylindrical steam reformer with various thermal conditions has been conducted. The bottom space of the cylindrical reactor was packed with Ruthenium (Ru) catalyst. A three-segment furnace was installed to create the axially variable boundary temperature distribution. Six K-type thermocouples were inserted into the catalyst layer, and three exhaust ports were fabricated on the side wall along the flow direction. The exhausted gases at each port were analyzed by using gas chromatograph (GC) system. The experimental results showed that the reforming reaction occurs intensively in the upstream region and more hydrogen is obtained when the intake gas is sufficiently heated up through the enhanced steam reforming (SR) reaction. The axially increasing boundary temperature setup provided the maximally accumulated reforming efficiency of 74.8%, when the reactor was placed at the 3rd section of the furnace.